The Symbolic Meaning of Upuh Ulen-Ulen Cloth in the Socio-Cultural Context of Central Aceh Society - Mufliah, Mufliah; Muharamsyah, Rambang; Khairani, Cut (Gondang: Jurnal Seni dan Budaya, 2024)
Upuh ulen-ulen cloth is traditional clothing of the Gayonese people which has a karawang gayo motif in it. The Karawang Gayo motif is philosophical and has various functions that are adapted to the lives of local people. The aims of this research are to 1) reveal the meaning of the upuh ulen ulen cloth in traditional marriages, 2) reveal the symbolic meaning of the upuh ulen ulen clothing, 3) reveal the cultural value of upuh ulen ulen in everyday life. The approach used in this research is descriptive qualitative. Data collection techniques are carried out through observation, interviews and documentation. The subjects in this research were 6 people consisting of Gayo cultural figures and artists, MAG commissioners, teachers, entrepreneurs (farmers), and tailors. From the results of data analysis, it was found that the use of upuh ulen ulen cloth in marriage means a change in status, starting from becoming a husband and wife, and also the parents' expectations for their child's household life. Apart from that, the symbolic meaning of the upuh ulen ulen cloth is related to each symbol which has a philosophical meaning in the life of the Gayo community. Meanwhile, the cultural values ​​contained in the upuh ulen ulen cloth include customs and also values ​​found in social life.